The impact of time pressure and type of fraud on susceptibility to online fraud - Lyu, Ce; Gao, Shenghan; Zhang, Qingqi (Frontiers in Psychology, 2025)
With the rapid development of the Internet, online fraud has evolved, posing a serious threat to people’s financial security. Susceptibility to online fraud refers to an individual’s vulnerability to Internet fraud, which was assessed in this study using the fraud material assessment paradigm. This study employed a 2 × 2 two-factor mixed experimental design to examine the effects of time pressure (present vs. absent) and fraud type (profit-taking vs. loss-avoidance) on susceptibility to online fraud. In the pre-study, real-life Internet fraud cases were adapted into legitimate and illegitimate materials, which were then rated. In the formal experiment, participants in the pressure group and control group assessed the legitimacy of these materials. The findings revealed that: (1) time pressure had a significant main effect, with participants exhibiting higher susceptibility to online fraud under time pressure than without it; (2) fraud type had a significant main effect, with susceptibility being higher for loss-avoidance fraud compared to profit-taking fraud; (3) a significant interaction effect was observed, where time pressure increased susceptibility to loss-avoidance fraud but had no significant effect on profit-taking fraud. These results suggest that time constraints and fraud types interact to influence an individual’s ability to resist online fraud. The findings provide insights for fraud prevention strategies, emphasizing the need to mitigate time pressure effects and educate individuals on different fraud types.